Bogor Water Adequacy Status for 2009-2019 - Nita Tarigan; Perdinan; Bambang Dwi Dasanto (Agromet, 2022)
Water adequacy becomes one of the global concerns as the trend of population growth continues to arise. The condition of water adequacy can be worse in some regions since it also relates to rainfall, which is greatly influenced by global climate change. Here we explore water adequacy at local scale especially in Bogor, Indonesia based on sectoral water demands. The study aims to analysis water adequacy for 2009-2019 based on a climatic water balance. Water supply-demand analysis was performed using water usage index (WUI) in which high WUI corresponds to high critical water balance. Our results showed there was a deceased trend for water supply in Bogor approximately 0.6% per year, whereas an increased trend was observed for water demand (1.7% per year). The main contributor for the increased demand was from domestic water demand by 48%. Generally, water adequacy in Bogor for the period analysis (2009 -2019) is still adequate, but a proper management of water resource will ensure water adequacy in the long run in response to population explosion and climate change.